A tecnologia da informação como instrumento para gestão estratégica hospitalar: um estudo de caso sobre a contribuição do Prontuário Eletrônico do Paciente - PEP - para a gestão hospitalar do hospital beneficente Maria Vitória - PE - Méllo, Antônio Charles Lucena de Oliveira (2013)
This study aims to identify the perception that managers Maria Victoria Hospital Society located in the state of Pernambuco has about the contribution of the Electronic Patient Record - PEP - for the strategic management of the Hospital. This work is focused on three major pillars, namely: Hospital Administration and its main features, Information Technology - IT as a strategic tool for the management and use of the Electronic Patient Record and its peculiarities. With regard to the methodology used, is a case study of the kind of research used as the means were bibliographic, documental and field. The findings raised will be used to contribute to the advancement in the field of public administration, more specifically, the managers' perception of the potential contribution of PEP as a strategic tool in the management of Maria Victoria Hospital.